If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3 = -3x + -1 Reorder the terms: -3 + 5x = -3x + -1 Reorder the terms: -3 + 5x = -1 + -3x Solving -3 + 5x = -1 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -3 + 5x + 3x = -1 + -3x + 3x Combine like terms: 5x + 3x = 8x -3 + 8x = -1 + -3x + 3x Combine like terms: -3x + 3x = 0 -3 + 8x = -1 + 0 -3 + 8x = -1 Add '3' to each side of the equation. -3 + 3 + 8x = -1 + 3 Combine like terms: -3 + 3 = 0 0 + 8x = -1 + 3 8x = -1 + 3 Combine like terms: -1 + 3 = 2 8x = 2 Divide each side by '8'. x = 0.25 Simplifying x = 0.25
| (X-7)+12=20 | | 7a-18=-3(-3+3)+7a | | x+15=4x-36 | | -40=b-51 | | H=7+27t-16t^2 | | x*15=4x-36 | | 6(x-11)=54x | | -9r-18r-3r=-12 | | 28=4s+r-s | | 4(3x+3)=3(5x+0.5) | | 1204.2528=2*3.14*6.8*6.8+2*3.14*6.8*h | | 4a-3a=a | | 0=x^2+2x+420 | | 4p+2=-3p+5p | | 4x+0.5= | | h=-2t^2+8t | | h=-2t^2+8tZ | | 17.18=3g+3.89 | | 11-3a=1-a | | lnx+ln(x-2)=0 | | (2x+5)*(3x+2)=0 | | 2*3.14=65.9 | | x-20=-69 | | 0=-4.9x^2+6 | | 33=-5(7x-5)+8(-8x+1) | | 12x-16=3x+8 | | x^2+14x-86=-6 | | x+26=-45 | | 12x-19=3x+27 | | (2x+10)=(5x-5) | | -2r=100 | | -2(b+4)+5(5-4b)=61 |